Rise in resident associational life in response to service delivery decline by urban councils in Zimbabwe (Commonwealth Journal of Local Governance, 2015)
This article links the decline of service delivery in urban councils in post-independence Zimbabwe to a rise in levels of associational life. Poorer urban residents cannot easily escape poor public sector service delivery by resorting to the private market. In response to declining service delivery by councils, ratepayers form residents’ associations to do three main things. First, they confront councils and pressure them to restore delivery capability. Second, they produce those services that councils are unable or unwilling to provide. Third, they defend residents against the predatory actions of councils. However, the capacities of residents’ associations in these three areas have yet to be established. Notably, limited formal opportunities exist for engagement between councils and residents’ associations which restricts their effectiveness. This paper argues that, if supported, residents’ associations can deepen local democracy while simultaneously facilitating the repair of councils’ capabilities – thus meeting disparate community demands and organising members to contribute to council recovery.